An efficient method for in vitro callus induction in Myrciaria dubia (Kunth) Mc Vaugh "Camu Camu" - Córdova, Ana M. (2014)
Due to the high variability in vitamin C production in Myrciaria dubia "camu camu", biotechnological procedures are necessary for mass clonal propagation of promising genotypes of this species. The aim was to establish an efficient method for in vitro callus induction from explants of M. dubia. Leaf and knot sex plants were obtained from branches grown in the laboratory and from fruit pulp collected in the field. These were desinfected and sown on Murashige-Skoog (1962) medium supplemented with 2,4-dichlorophenoxyacetic acid (2,4-D), benzylaminopurine (BAP) and kinetin(Kin). The cultures were maintained at 25±2°C in darkness for 2 weeks and subsequently with a photoperiod of 16 hours in light and 8 hours in dark for 6 weeks. Treatment with 2 mg/L 2,4-D and 0.1 mg/L BAP allowed major callus formation in the three types of explants. Calluswere generated from the first week (knots), fourth week (leaves) and sixth week (pulp) and these were friable (leaves and nodes) and non-friable (pulp). In conclusion, the described method is efficient for in vitro callus induction in leaves, knots and pulp of M. dubia, been leaves and knots explants more suitable for callus obtention.